Recognizing the rapid expansion of rubber plantation: A threat to native forest in parts of Northeast India - Chakraborty Kasturi; Das A.K; Raju P.L.N; Sarma K.K; Sudhakar S (Current Science, 2018)
With the current trend of land use/land cover (LULC) change taking place globally, several parts of north-east India are also showing signs of change in LULC pattern leading to forest loss. This study focusses on the expansion of monoculture rubber plantation (Hevea brasiliensis) in selected sub-watersheds in northeast India, and distributed in parts of north Tripura, Mizoram and major portion in the Karimganj district of Assam. Remote sensing and GIS technique has been used to map and analyse the extent of rubber plantation using temporal IRS LISS III satellite data from 1997 to 2013. It has been observed that rubber plantation increased from 4.47 sq. km to 28.42 sq. km in various parts of the study area. The expansion was more rapid during recent times, i.e. during 2010 to 2013. The plantation took place in dense forest, open forest and degraded forest areas. The spread of the plantation was also observed in one reserved forest located within the study area. There are several instances of negative impacts of rubber plantation expansion in Southeast Asia. Similar expansion of rubber plantation has been observed in northeast India as well. Further spread of rubber plantations in the region needs to be regulated to avoid conversion of dense and reserved forest areas by fostering use of mixed cropping methods instead of rubber monocultures, and by adopting more sustainable land use and management practices.
Keywords: GIS; Northeast India; Remote sensing; Rubber plantation